1996
DOI: 10.1097/00006454-199609000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy, safety and toleration of azithromycin vs. penicillin V in the treatment of acute streptococcal pharyngitis in children: results of a multicenter, open comparative study

Abstract: In the present study on GABHS pharyngitis in children, a once daily (10-mg/kg), 3-day oral regimen of azithromycin was as clinically effective and as safe as traditional penicillin but appeared inferior in eliminating GABHS from the throat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 15 publications
0
17
2
1
Order By: Relevance
“…In our work, the number of GAS isolates (7 of 135) that developed resistance to macrolides after low-dose azithromycin treatment was strikingly high (8). This phenomenon was not observed in three recent clinical trials of azythromycin treatment in patients with tonsillopharyngitis (4,16,18). In two studies (4, 18) the susceptibilities of the posttreatment isolates were not reported.…”
Section: Discussioncontrasting
confidence: 44%
“…In our work, the number of GAS isolates (7 of 135) that developed resistance to macrolides after low-dose azithromycin treatment was strikingly high (8). This phenomenon was not observed in three recent clinical trials of azythromycin treatment in patients with tonsillopharyngitis (4,16,18). In two studies (4, 18) the susceptibilities of the posttreatment isolates were not reported.…”
Section: Discussioncontrasting
confidence: 44%
“…First, it is not known if the dose of AZM in this study is optimum. The dose of AZM used in this study, 10 mg/kg for children, may be insufficient [18], although both 10 or 20 mg/kg/day for 3 days has been shown to be equally safe and effective [9]. Another study indicated that 10 mg/kg was associated with a higher bacteriological relapse and an increased risk of bacteria gaining resistance in comparison with 20 mg/kg [13].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, a longer treatment period may increase the risk of carriage of resistant S. pneumoniae strains [17]. A 3-day course of AZM, another alternative to penicillin, has been shown to have efficacy comparable with that of a 10-day course of penicillin V [18]. In this context, the importance of our study lies in comparison of the efficacy of the alternative treatments, a newer cephalosporin and AZM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of macrolides in the treatment of pharyngitis has been studied in several clinical trials [32,38,39,41,45,47,50,52,54]. These trials showed that in a 10-day treatment, erythromycin and cefprozil produced clinical response rates of 91% and 95%, respectively [45].…”
Section: Clinical Trialsmentioning
confidence: 99%